Validation of the RHL30 digital gene expression assay as a prognostic biomarker for relapsed Hodgkin lymphoma. (8th June 2020) - Calvente, Lourdes; Tremblay‐LeMay, Rosemarie; Xu, Wei; Chan, Fong Chun; Hong, Michael; Zhang, Tong; Yhim, Ho‐Young; Kuruvilla, John; Crump, Michael; Kukreti, Vishal; Prica, Anca; Regier, Dean; et al.
Summary: Despite continuing improvements in the management of classical Hodgkin lymphoma (cHL), relapse remains associated with a risk of lymphoma‐related mortality. The biological composition of relapse tumour biopsies shows interpatient variability, which can be leveraged to design prognostic biomarkers. Here, we validated the RHL30 assay, a previously reported gene expression model in an independent cohort of 41 patients with relapsed cHL. Patients classified as high‐risk by the RHL30 assay had inferior failure‐free survival (FFS) after autologous stem cell transplantation (2‐year FFS 41% vs. 92%, P  = 0·035). The RHL30 model is a robust biomarker that risk‐stratifies patients considered for autologous stem cell transplantation.